“I Can’t Do All This—This Is Nuts!”: An Ethnographic Account of the Challenges Posed by Vajrayāna Deity Yoga in a Western Context - Perkins, Sophie-Anne (Religions, 2023)
This article provides an in-depth exploration of the contextual, epistemic, ethical, personal, practical, religious, and socio-cultural factors that sixteen Western practitioners of Vajrayāna Buddhism highlighted as having particularly challenged their ability to learn and engage in deity yoga, including what strategies they may have adopted in attempting to overcome their impact. While these have been largely overlooked by empirical research on meditation, their pertinence to understanding practice efficacy and outcome, as well as the phenomenological unfolding of particularly adverse practice-related experiences, have recently been recognized alongside the prevalence of the latter. In addition, these practitioner testimonies shed light on how the cross-cultural transmission of Vajrayāna Buddhism involves a process in which practice approaches and environments are undergoing adaptation and negotiation in light of the needs and lifestyles of lay practitioners, while meaning is being synthesized through their responses to the experiences that unfold not only from their exposure to teachers and their teachings but also from their engagement in tantric practice.